Consumidores compulsivos diante da perda do poder aquisitivo: um estudo de caso - Guerra, Danilo Pinheiro (2017)
The present investigation contemplates a case study that involves the compulsive consumers in the face of the loss of purchasing power with the objective of contributing to the development of the understanding of the subject of compulsive buying. More specifically, it seeks to identify how the compulsive consumer is able to deal with the restriction of consumption imposed by the loss of purchasing power and to classify the greater and lesser propensity to the compulsive effect on purchases. As a methodological resource, qualitative and descriptive techniques were used. The data collection was carried out in 4 clinical practices of psychologists and psychoanalysts during the month of September 2017. This way, it was explored the testimony of professionals who deal with consumers who present compulsive behavior in the face of loss of purchasing power. The results of the research indicate that the compulsive consumers are indifferent to the restriction of a more limiting budget, since the behavior of the consumers is subject to cognitive, emotional biases and social influences.